An evaluation of patient satisfaction with pharmaceutical services at Munyang Kute Regional General Hospital - Bengimiate, Nuriza; Hartopo, Haqi; Razoki, Razoki; Ginting, Astriani Natalia Br (Buletin Kedokteran & Kesehatan Prima, 2025)
Patient satisfaction is a crucial indicator for assessing hospital service quality, in which pharmaceutical services play a vital role as a primary point of contact with patients. This study aimed to comprehensively evaluate the satisfaction level of outpatients with the pharmaceutical services at Munyang Kute Regional General Hospital. This research employed a descriptive quantitative design with a cross-sectional approach. A total of 90 respondents were selected through a purposive sampling technique based on predetermined criteria. The research instrument was an adapted questionnaire designed to measure satisfaction across five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. The collected data were analyzed descriptively using SPSS software. The findings indicated that patients were generally satisfied with the pharmaceutical services they received. The highest level of satisfaction was observed in the responsiveness dimension, with a percentage of 69.72%. The other dimensions, in descending order, were tangibles (32.21%), empathy (27.19%), assurance (19.60%), and the lowest was the reliability dimension (16.00%). Overall, the patient perception of pharmaceutical services at Munyang Kute Regional General Hospital is positive. Nevertheless, there remains room for improvement, particularly in the reliability and assurance dimensions. Continuous quality improvement through enhanced patient education and optimization of facilities is highly recommended.